The role of social lending in financial inclusion - Solarz, Małgorzata (Rola social lendingu w inkluzji finansowej, 2011)
Financial exclusion affects some social groups and constitutes one of the contemporary challenges. Activities aimed at preventing and solving this major social and economic problem are referred to as financial inclusion. Changes in the financial market resulted in the appearance of social lending in Poland three years ago. It represents a modern form of entering into loan agreements between those who are in need of financial resources and investors taking advantage of the Internet facilities, without the involvement of banks. The analysis performed indicates that social lending helps, to some extent, limit the occurrence of financial exclusion, but at the same time this tool is far from perfect
Nauki o Finansach = Financial Sciences, 2011, Nr 1 (6), s. 179-182
Keywords: social lending; financial exclusion; financial inclusion